Applications of CRISPR–Cas in agriculture and plant biotechnology - Zhu, Haocheng; Li, Chao; Gao, Caixia (Nature reviews. Molecular cell biology, 2020)
The prokaryote-derived CRISPR–Cas genome editing technology has altered plant molecular biology beyond all expectations. Characterized by robustness and high target specificity and programmability, CRISPR–Cas allows precise genetic manipulation of crop species, which provides the opportunity to create germplasms with beneficial traits and to develop novel, more sustainable agricultural systems. Furthermore, the numerous emerging biotechnologies based on CRISPR–Cas platforms have expanded the toolbox of fundamental research and plant synthetic biology. In this Review, we first briefly describe gene editing by CRISPR–Cas, focusing on the newest, precise gene editing technologies such as base editing and prime editing. We then discuss the most important applications of CRISPR–Cas in increasing plant yield, quality, disease resistance and herbicide resistance, breeding and accelerated domestication. We also highlight the most recent breakthroughs in CRISPR–Cas-related plant biotechnologies, including CRISPR–Cas reagent delivery, gene regulation, multiplexed gene editing and mutagenesis and directed evolution technologies. Finally, we discuss prospective applications of this game-changing technology. The newest CRISPR–Cas genome editing technologies enable precise and simplified formation of crops with increased yield, quality, disease resistance and herbicide resistance, as well as accelerated domestication. Recent breakthroughs in CRISPR–Cas plant biotechnologies improve reagent delivery, gene regulation, multiplexed gene editing and directed evolution.